2000
DOI: 10.1046/j.1469-7580.2000.19740659.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical re‐evaluation of the process of cavitation in the rat knee joint: cellular and cell strata alterations in the interzone

Abstract: To assess the contribution of apoptosis to the mechanism of synovial joint cavitation, and to clarify morphological cellular changes during cavitation, we investigated the development of the rat knee joint by light and electron microscopy, TUNEL methods, and electrophoresis of DNA fragments. Although cavitation occurred within the interzone, which consists of 2 outer and a middle layer termed the intermediate zone, no morphological or biochemical signs of cell death, in particular apoptosis, were seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 34 publications
5
77
1
Order By: Relevance
“…In spite of lack of detailed information, these hypotheses have been directly adopted on the mechanism of cavity formation in the TMJ, which is categorized in secondary cartilaginous joints such as sternoclavicular and acromioclavicular joints. For instance, many researchers have failed to find apoptosis at the cavity-forming area in long bone joints (Ballard and Holt, 1968;Murray and Drachman, 1969;Mitrovic, 1977Mitrovic, , 1978Mori et al, 1995;Nalin et al, 1995;Kimura and Shiota, 1996;Kavanagh et al, 2002), while some studies have detected it (Abu-Hijleh et al, 1997;Ito and Kida, 2000). Matsuda et al (1997) revealed no detection of apoptosis in this area by biochemical and histochemical analyses with the TUNEL method in TMJ development, consistent with the present observations.…”
Section: Discussionsupporting
confidence: 81%
“…In spite of lack of detailed information, these hypotheses have been directly adopted on the mechanism of cavity formation in the TMJ, which is categorized in secondary cartilaginous joints such as sternoclavicular and acromioclavicular joints. For instance, many researchers have failed to find apoptosis at the cavity-forming area in long bone joints (Ballard and Holt, 1968;Murray and Drachman, 1969;Mitrovic, 1977Mitrovic, , 1978Mori et al, 1995;Nalin et al, 1995;Kimura and Shiota, 1996;Kavanagh et al, 2002), while some studies have detected it (Abu-Hijleh et al, 1997;Ito and Kida, 2000). Matsuda et al (1997) revealed no detection of apoptosis in this area by biochemical and histochemical analyses with the TUNEL method in TMJ development, consistent with the present observations.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, the possibility of a role of cell death in joint formation has been questioned (Ito and Kida, 2000;Archer et al, 2003).…”
Section: Cell Death In Joint Formationmentioning
confidence: 99%
“…This view was challenged by several authors who assumed that articular cartilage is formed by the cells lying at the periphery of the cavitated joint and derived from the cells of interzone [4,8,28]. The authors of these publications showed that the interzone is ultrastructurally distinguishable into 2 outer layers contiguous to the epiphyseal ends and a thin central intermediate zone.…”
Section: Formation Of Articular Cartilagementioning
confidence: 90%
“…WNT14 expression seems to be sufficient to direct joint development as judged by its ability to induce and/or maintain a panel of gene interzone by clearing up the cells with chondroblastic potentialities. In another study, however, cell death was not observed during cavitation of the developing joints in rat or rabbit knee [28,31]. Macrophages were present prior to cavitation in the periphery of joint interzones but not at the presumptive joint line in the central region of interzone [14].…”
Section: Joint Cavitationmentioning
confidence: 99%